Water geochemistry, Jarvis Creek watershed, Interior Alaska, 2011-2016 - Thomas Douglas; Tiffany Gatesman (Arctic Data Center, 2022)
The overall project assessed the linkages and controls of a subarctic glacier-permafrost hydrological system from a watershed-scale perspective using field measurements, remote sensing and numerical modeling. Jarvis Creek (634km² (kilometers squared)), which feeds the Delta and Tanana River in Interior Alaska, was studied as a proxy of the observed mountain glacier melting and permafrost degradation that has been documented across the Arctic region in recent decades. The specific objectives were to 1) assess the hydrologic fluxes (including streamflow source components), stores, pathways and the role of glacier wastage on watershed hydrology, through hydrologic and geochemical field measurements as well as numerical and statistical modeling; 2) quantify the effect of glaciers and permafrost on recent historical (1960-present) hydrologic fluxes and storage by combining remote sensing, field measurements of glacier mass balance, and hydrology with a heat- and mass transfer model, and 3) project the future hydrologic regime using custom-derived downscaled climate projections. The purpose of this dataset was to measure geochemistry. Bulk streamflow water samples were collected daily from the lowlands of Jarvis Creek (634 km², 3.3% glacier cover) throughout the flow season (late April through September) during 2011-2016. Synoptic sampling of source waters included rain, snow, headwater late-winter streamflow and late-summer glacier terminus discharge. All 1,227 source water and bulk streamflow samples were analyzed for stable water isotopes (δ18O (Oxygen-18) and δD (Deuterium)) and dissolved ion concentrations (SO4²- (sulfate) :Cl- (chlorine) ratio).